Development of Central Bank - Puspita, Dhini; Silka Faroida; Rahma Atia Rizqi; Rinda Asytuti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This paper aims to explain the development of central banks by formulating the following questions: How has the Status of Central Banks Developed?, What is the Position of the Central Bank?, What is the Relationship between Central Banks and Financial Institutions in Developed and Developing Countries? This paper uses a qualitative approach, because the data sources and research results are in the form of library research The result of this research is that the central bank is an institution that has an important role in the economy of a nation, especially in the monetary sector. a nation, especially in the fields of monetary, finance, and banking. The purpose of the central bank as stated in the Law of the Republic of Indonesia No. 23 Year 1999 Chapter 3 Article 7 is to achieve and maintain rupiah stability. maintain rupiah stability.In accordance with the BI Law, Bank Indonesia serves as an independent state institution.independent in carrying out its duties and authorities, free from interference from the government, and other parties, except for the government, and other parties, except for matters expressly regulated in the law.the law. Bank Indonesia's relationship with the government has been clearly regulated in Law No. 23/1999 on Bank Indonesia. 23 of 1999 concerning Bank Indonesia, namely that Bank Indonesia is still designated as the government's cash holder. holder of the government's treasury.